2014
DOI: 10.1177/1060028014533303
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Renal Toxicity in Cancer Patients Receiving Cisplatin With and Without Mannitol

Abstract: When limited quantities of mannitol are available, it should preferentially be given to patients at particularly high risk of nephrotoxicity. Our analysis suggests that those patients receiving the dosing schedule of 100 mg/m cisplatin every 3 weeks and those with hypertension are at the greatest risk of nephrotoxicity and would benefit from the addition of mannitol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 7 publications
2
54
1
1
Order By: Relevance
“…Another study, with 390 patients admitted to a medical intensive care unit for septic shock, also showed an association between anti-hypertensive treatment and the development of acute kidney injury 22. Concerning hypertension, a recent study involving cancer patients receiving cisplatin with or without mannitol as nephroprotectant showed that patients with a previous history of hypertension had a higher likelihood of developing nephrotoxicity 23. Another workgroup constructed a predictive model for the occurrence of acute kidney injury after the first course of cisplatin, in which previous history of hypertension was included 24.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, with 390 patients admitted to a medical intensive care unit for septic shock, also showed an association between anti-hypertensive treatment and the development of acute kidney injury 22. Concerning hypertension, a recent study involving cancer patients receiving cisplatin with or without mannitol as nephroprotectant showed that patients with a previous history of hypertension had a higher likelihood of developing nephrotoxicity 23. Another workgroup constructed a predictive model for the occurrence of acute kidney injury after the first course of cisplatin, in which previous history of hypertension was included 24.…”
Section: Discussionmentioning
confidence: 99%
“…B. mit Iohexol für unabdingbar erachten [30]. Bei wiederholten Cisplatindosen von >100 mg/m 2 ist die Gabe von Mannitol mit einem verminderten Auftreten von AKI assoziiert [55]. Eine Präventionsmaßnahme für Patienten mit einem hohen Risiko für ein Tumorlysesyndrom ist die Gabe von Xanthinoxidaseinhibitoren [74].…”
Section: Patienten Mit Hämato-onkologischen Erkrankungenunclassified
“…Clinical manifestations of cisplatin‐induced nephrotoxicity include decreased glomerular filtration, increased serum creatinine and reduced levels of serum magnesium and potassium . Greater risk has been reported with increased dose and frequency of cisplatin administration . Mechanistically, cisplatin‐associated nephrotoxicity has been attributed to the activation of complex signalling pathways that lead to injury and death of renal tubule cells .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…[7][8][9] Greater risk has been reported with increased dose and frequency of cisplatin administration. 10 Mechanistically, cisplatin-associated nephrotoxicity has been attributed to the activation of complex signalling pathways that lead to injury and death of renal tubule cells. 7 Cisplatin has also been shown to incite local inflammation, further contributing to tubule damage.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation